Setting Up an Undergraduate Immunology Lab: Resources and Examples - Garrison, Keith E.; Gubbels Bupp, Melanie R. (Frontiers in Immunology, 2019)
Laboratory courses in immunology require a different skill set for their development than lecture courses. They vary widely in their form based on factors like institutional budget and class size, and also in the prioritization of learning goals centered around reinforcing lecture concepts and/or building fundamental skills in the field of immunology. Lab activities can come from a variety of sources including: published research protocols, commercial kits, computer-based tools or simulations, and case studies. Each has their own strengths which will be explored here. There are also important decisions to make about how students will report their data, and what level of guidance in interpreting data is best to enhance student learning and growth. Finally, methods like use of rubrics can help ensure fair and efficient grading, especially with skills-based learning goals. Periodic assessment is important to ensure that activities contribute effectively to student learning and to guide improvements to the lab course over time.